An examination of the impact of 4-H onemployability skills - Wendt, Jody (My University, 2019)
4-H is a national non-profit youth organization that was started with the idea of connecting public school education to country life. The motto of the 4-H organization is to make the best better. 4-H programs focus on hands-on, practical methods for young people. Topic areas include health, science, agriculture, and citizenship. These areas are centered around the 4 H’s: Head, Heart, Hands, and Health. Creating positive environments where adults serve as mentors to guide youth along their educational journeys is the main design in each of the delivery modes: after-school programming, in-school enrichment programming, clubs, and camps. Measuring the impact of the 4-H program’s ability to increase participants’ life skills is one of the biggest challenges. The purpose of this research study is to investigate such impact by surveying past 4-H participants. Did 4-H alumni’s participation in 4-H give them the employability skills needed to enter the agriculture sector? An online survey research method is utilized to gather anonymous responses from 4-H alumni. Results indicate that 4-H participants have gained employability skills through their 4-H experiences to help make them successful in the agriculture industry. These results help validate the efforts being made by the Nebraska 4-H program in regards to providing hands-on learning experiences to gain such employability skills.
Keywords: 4-H; Employability Skills; Youth Organizations; Impact Analysis